Sire breed effects on economic efficiency of a terminal-cross beef production system - G.M. Smith; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1977)
This article was abstracted from a manuscript by Gerald H. Smith, U.S. Meat Animal Research Center, Clay Center, Nebraska which appeared in the December, 1976, issue of the Journal of Animal Science. The carcass and meats research data for the study were coordinated by Dr. Michael E. Dikeman, Kansas State University, so permission was granted to present results of that study here. Performance and carcass characteristics of the cattle were presented in the 1975 Cattlemen's Day Report.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Terminal-cross; Performance; Carcass characteristics